The Use of Probiotic Therapy in Metabolic and Neurological Diseases - Lee, Shirley H. F.; Ahmad, Siti R.; Lim, Ya C.; Zulkipli, Ihsan N. (Frontiers in Nutrition, 2022)
The human gut is home to trillions of microbes that interact with host cells to influence and contribute to body functions. The number of scientific studies focused on the gut microbiome has exponentially increased in recent years. Studies investigating factors that may potentially affect the gut microbiome and may be used for therapeutic purposes in diseases where dysbioses in the gut microbiome have been shown are of particular interest. This review compiles current evidence available in the scientific literature on the use of probiotics to treat metabolic diseases and autism spectrum disorders to analyse the efficacy of probiotics in these diseases. In order to do this, we must first define the healthy gut microbiome before looking at the interplay between the gut microbiome and diseases, and how probiotics affect this interaction. In metabolic diseases such as obesity and diabetes, probiotic supplementation positively impacts pathological parameters. Conversely, the gut-brain axis significantly impacts neurodevelopmental disorders such as autism spectrum disorders. However, manipulating the gut microbiome and disease symptoms using probiotics has less pronounced effects in neurodevelopmental diseases. This may be due to a more complex interplay between genetics and the environment in these diseases. In conclusion, the use of microbe-based probiotic therapy may potentially have beneficial effects in ameliorating the pathology of various diseases. Validation of available data for the development of personalised treatment regimens for affected patients is still required.